Immunomodulatory Activity of the Marine Sponge, Haliclona (Soestella) sp. (Haplosclerida: Chalinidae), from Sri Lanka in Wistar Albino Rats: Immunosuppression and Th1-Skewed Cytokine Response - Gunathilake, Varuni; Bertolino, Marco; Bavestrello, Giorgio; Udagama, Preethi (Journal of Immunology Research, 2020)
Natural secondary metabolites of sponges of the genus Haliclona are associated with an array of biological activity with therapeutic usage. We investigated the immunopharmacological properties of a presumably novel marine sponge species from Sri Lanka, Haliclona (Soestella) sp. Sponge material was collected from southern Sri Lanka by scuba diving. Sponge identiﬁcation was based on spicule and skeleton morphology using light microscopy. Selected in vivo and ex vivo tests investigated nonfunctional and functional immunomodulatory activity of the Haliclona (Soestella) sp. crude extract (HSCE) in the Wistar rat model. Compared to the controls, rats orally gavaged daily for 14 consecutive days with 15mg/kg dose of the HSCE manifested a signiﬁcant reduction of immune cell counts of total WBCs (by 17%; p<0 :01), lymphocytes (38%), platelets (52%), splenocytes (20%), and bone marrow cells (BMC; 60%) (p<0 :001), with a concurrent increase in the neutrophil:lymphocyte ratio (p<0 :05); RBC counts abated by 53% (p<0 :001). A signiﬁcant reduction of the splenosomatic index was evident with the 10 and 15mg/kg doses (p<0 :001). Rat plasma TNF-α cytokine level was augmented by tenfold (p<0 :001), IL-6 level by twofold (p<0 :01) with the 15mg/kg HSCE treatment, while IL-10 was detectable in rat plasma only with this treatment; the corresponding Th1:Th2 cytokine ratio (TNF-α:IL-10) was indicative of an unequivocal Th1-skewed cytokine response (p<0 :01). Ex vivo bone marrow cell and splenocyte proliferation were signiﬁcantly and dose dependently impaired by HSCE (IC50 0.719 and 0.931μg/mL, respectively; p<0 :05). Subacute toxicity testing established that HSCE was devoid of general toxic, hepatotoxic, and nephrotoxic eﬀects. In conclusion, HSCE was orally active, nontoxic, and eﬀectively suppressed nonfunctional and functional immunological parameters of Wistar rats, suggestive of the potential use of the HSCE as an immunosuppressant drug lead.
Keywords: Marine Sponge; Haliclona (Soestella) sp.; Immunosuppression; Th1-Skewed Cytokine Response